Chirality and Chiroptical Effects in Metal Nanostructures: Fundamentals and Current Trends. Issue 16 (1st August 2017) - Collins, Joel T.; Kuppe, Christian; Hooper, David C.; Sibilia, Concita; Centini, Marco; Valev, Ventsislav K.
Abstract : Throughout the 19 th and 20 th century, chirality has mostly been associated with chemistry. However, while chirality can be very useful for understanding molecules, molecules are not well suited for understanding chirality. Indeed, the size of atoms, the length of molecular bonds and the orientations of orbitals cannot be varied at will. It is therefore difficult to study the emergence and evolution of chirality in molecules, as a function of geometrical parameters. By contrast, chiral metal nanostructures offer an unprecedented flexibility of design. Modern nanofabrication allows chiral metal nanoparticles to tune the geometric and optical chirality parameters, which are key for properties such as negative refractive index and superchiral light. Chiral meta/nano‐materials are promising for numerous technological applications, such as chiral molecular sensing, separation and synthesis, super‐resolution imaging, nanorobotics, and ultra‐thin broadband optical components for chiral light. This review covers some of the fundamentals and highlights recent trends. We begin by discussing linear chiroptical effects. We then survey the design of modern chiral materials. Next, the emergence and use of chirality parameters are summarized. In the following part, we cover the properties of nonlinear chiroptical materials. Finally, in the conclusion section, we point out current limitations and future directions of development. Abstract : Chiral metal nanostructures have allowed unprecedented control over chiroptical effects . The flexibility in design in novel nanofabrication techniques has resulted in a proliferation of new chiral nanomaterials. These nanomaterials are now shaping up numerous emerging research trends that offer promising practical applications and deep insights into fundamental scientific questions.